Experimental evaluation of laser cut quality of glass fibre reinforced plastic composite - Choudhury, I.A.; Chuan, P.C. (Elsevier, 2013)
Fibre reinforced plastic is a high strength and low weight material and is often used in aerospace industry., or even as our everyday products. The traditional machining of this material is difficult as the tool will continuously encounter alternate matrix and fibre materials, whose response to machining can vary greatly. Because of this, a noncontact material removal process like laser machining offers an attractive alternative. The objective of this study is to assess the quality of cut surface of glass fibre reinforced plastic by single-pass and double-pass laser beam. A first-order orthogonal design has been adopted to conduct experiments where the nozzle diameter, material thickness, and cutting speed were the input laser variables and the roughness of the cut surface and kerf width at the irradiation and exit sides were the output. The results show that the quality of cut surface produced by double-pass beam appeared to be much better than that produced by a single-pass laser beam. The model equations developed indicate that the effects of input variables on the output are different in single-pass beam and double-pass beam. The double-pass beam produced lower kerf width compared to single-pass beam and kerf width was smaller at the exit side. WHile the single-pass beam produced better surface finish than the double-pass beam. Moreover the effect of nozzle diameter on both the surface roughness and kerf width were found to be significant. The surface finish and kerf width were better when the nozzle diameter was smaller.